SISTEM INFORMASI USAHA MIKRO KECIL DAN MENENGAH KABUPATEN BATANGHARI PADA DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN - Mulyati , Sri; Mayola, Sisi; -, Tamrinsyah (JURNAL AKADEMIKA, 2023)
Micro, Small and Medium Enterprises in Batanghari is one important part of the economy in Batanghari. Changing times, a lot of people can make their own efforts. Along with the many businesses in the distric of Batanghari so many businesses doing promotions for their business continuity. In line with this web-based information system that can hold information about the micro, small, and medium enterprises based web can be a mass promotion for SMEs in Batanghari.